الإبداع الوظيفي كمدخل لتحسين أداء الموارد البشرية في ظل التغيرات البيئية لمنظمات الأعمال - عبدالجبار، سهيلة; بياض، مصطفى (جامعة العلوم الإسلامية العالمية - عمادة البحث العلمي, 2019)
يتزايد الاهتمام بموضوع الإبداع في ظل التحديات التي تفرضها ظاهرة العولمة والمنافسة الشديدة وثورة المعلومات، لأنه أصبح أمراً ضرورياً وحيوياً للمؤسسة وليس مجرد أمر ثانوي، ولهذا ظهرت حاجة المؤسسات للإبداع بطرق مختلفة وبدرجات متفاوتة من الاهتمام والعناية. ويعتبر مطلباً رئيسياً ومؤشراً يستدل من خلاله على نجاح المؤسسات أو فشلها في تحقيق أهدافها من أجل النهوض بمستوى أداء أفرادها، لذلك ينبغي تقدير أهمية ودور الإبداع الوظيفي من خلال الجهود المبذولة لتوفير مناخ ملائم، يمكن للموظفين من إظهار ما لديهم من قدرات ومهارات إبداعية، والاستغلال الأمثل مما يدفعهم للعمل والبحث عن حلول للمشكلات التي تواجههم بصورة إبداعية من أجل الارتقاء بمستوى الأداء الوظيفي للمؤسسة أو لأفراد. وعليه سوف نركز في بحثنا على أثر الإبداع الوظيفي على أداء الموارد البشرية في المؤسسة، مع اسقاط الجانب النظري على الواقع المؤسساتي أيضاً من خلال دراستنا، وذلك بالاعتماد على المنهج التحليلي في تحليل البيانات والمعلومات المحصل عليها باستعمال أداة الاستبيان، ومن ثم تحديد النتائج المتواصل إليها.
In light of the challenges posed by the phenomenon of globalization, intense competition and the information revolution, the issue of creativity is becoming more and more important because it has become necessary and vital for the institution, not just a secondary matter. Therefore, institutions need to innovate in different ways with varying degrees of attention and care. It is a major demand and an indicator of the success or failure of institutions to achieve their goals in order to improve the performance of their personnel. The importance and role of functional creativity should be appreciated through efforts to provide an adequate environment that enables employees to demonstrate their creative abilities and skills; prompting them to work and find solutions to the problems, they face creatively in order to improve the performance of the institution or individuals. In this context, we will focus on the impact of functional creativity on the performance of human resources in the institution, while also shedding the theoretical aspect on the institutional reality through our study, based on the analytical approach in analyzing the data and information obtained using the questionnaire tool and then determining the results achieved.
Keywords: الإبداع الوظيفي -- الموارد البشرية -- التغيرات البيئية